YAP1 inhibits ovarian endometriosis stromal cell invasion through ESR2. Issue 3 (September 2020) - Zeng, Cheng; Wu, Pei-Li; Dong, Zhao-Tong; Li, Xin; Zhou, Ying-Fang; Xue, Qing
Abstract : Endometriosis is an estrogen-dependent disease, and estrogen receptor 2 ( ESR2 ) plays a critical role in the pathogenesis of ovarian endometriosis by promoting cell invasion. Yes-associated protein 1 ( YAP1 ) plays suppressive roles in several types of tumors. However, the relationship between YAP1 and ESR2 is not fully understood. The aim of this study was to investigate the regulatory mechanism of YAP1 in terms of ESR2 and YAP1 regulation of endometriotic stromal cell (ECSC) invasion in ovarian endometriosis. Our results demonstrated that YAP1 mRNA and protein levels in eutopic endometrium (EU) tissues were higher than those in paired ectopic endometrium (EC) tissues. ECSCs transfected with siYAP1 exhibited a significant increase in both ESR2 mRNA levels and protein expression. Simultaneously, YAP1 overexpression in ECSCs yielded the opposite results. Co-IP assays demonstrated YAP1-NuRD complex formation by YAP1, CHD4 and MTA1 in ECSCs. YAP1 bound to two sites, (-539, -533) and (-158, -152), upstream of the ESR2 transcription initiation site. YAP1 binding to the two sites of the ESR2 promoter in ECSCs was significantly lower than that in eutopic endometrial stromal cells (EUSCs) from EU tissues. ECSCs transfected with siYAP1 exhibited increased invasion activity, while ECSCs transfected with siESR2 showed inhibition of invasion. However, transfection with siYAP1 and siESR2 together decreased the number of invading cells compared with transfection with siYAP1 alone. Therefore, we conclude that decreased levels of YAP1 in ovarian endometriomas enhance ESR2 expression via formation of a YAP1-NuRD complex, which further binds to the ESR2 promoters. Furthermore, YAP1 inhibits ECSCs invasion.